Analysis and Mitigation of the Impact of Artisanal Gold Mining in Ratatotok Village, Southeast Minahasa Regency - Octavina, Beatrix; Riogilang, Herawati; Thambas, Arthur Harris (CV. Green Publisher Indonesia, 2025)
Artisanal gold mining in Ratatotok Village, Southeast Minahasa Regency, is an informally growing economic activity that poses significant environmental impacts, particularly on water quality. The use of hazardous chemicals such as mercury (Hg) and cyanide (CN), along with the potential release of arsenic (As), presents a serious threat to groundwater, springs, and rivers utilized by local communities. This study aims to assess water quality by focusing on three key parameters—mercury, cyanide, and arsenic—based on the quality standards stipulated in Government Regulation No. 2 of 2023 (for clean water) and Government Regulation No. 22 of 2021 (for Class III river water). Spatial analysis was conducted using a 500-meter buffer radius from seven sampling points to map pollutant distribution and identify zones of contamination risk. Laboratory results indicate that although all parameter concentrations remain within regulatory thresholds, the levels of arsenic and cyanide at several locations approach the upper limits, suggesting the onset of contamination. Spatial mapping reveals moderate-risk zones concentrated around mining activity areas, warranting targeted mitigation efforts. As a mitigation strategy, this study recommends the implementation of a modular reactor system with cyanide recirculation. This simple and environmentally friendly waste processing technology enables the reuse of cyanide solution in a closed-loop system. Through quantitative and spatial approaches, this study is expected to contribute to the formulation of environmental management policies and adaptive water pollution mitigation strategies tailored to the context of artisanal gold mining areas